Lower scaling approximation to EOM-CCSD: a critical assessment of the ionization problem - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2018)
In this article, we investigate the performance of different approximate variants of the EOM-CCSD method for calculation of ionization potential (IP), as compared to EOM-CCSDT reference values. None of the lower scaling approximations to the EOM-CCSD method give a consistent performance for valence, inner valence, and core ionization, favoring one, or the other depending on the nature of the approximation used. The parent EOMIP-CCSD method gives superior performance for valence IP but can show large errors for inner valence and core ionization. The problem is particularly severe for core-ionization, where even the EOMIP-CCSDT method cannot provide quantitative accuracy.
Keywords: EOM-CCSD; Ionization potential; lower scaling